Winter University 2018 Brownfield (Re)Development: New Perspectives for Zaton - Nuianzina, Valeriia; Kostrubova, Alexandra (project baikal, 2018)
The article features the methodology of the International Baikal Winter University of Urban Planning Design, the topics and the teams that participated in the 19th session. The article describes the site, the technical assignment and the work of the teams. It underlines the significance of abundant territories as hidden resources for urban development.